Sutton Hoo a seventh-century princely burial ground and its context - Carver, Martin Oswald Hugh 1941- (The British Museum Press, 2005)
This book brings the excavations at the fabulous site of Sutton Hoo right up-to-date, documenting the discoveries made since 1983. It also takes a fresh look at what was known prior to this and includes discussions by contributing experts.
Keywords: Geschichte 700-1000; Geschichte 1983-2001; Archeologische vondsten; Grafvelden; Koningen (vorsten); Funde; Anglo-Saxons -- Kings and rulers -- Death and burial; Burial -- England -- Suffolk; Excavations (Archaeology) -- England -- Suffolk; Ship burials -- England -- Suffolk; Ausgrabung; Suffolk (England) -- Antiquities; Sutton Hoo Ship Burial (England); Sutton Hoo; Bildband; Inventar